1989
DOI: 10.1135/cccc19890321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the kinetics of bisphenol A synthesis on promoted and unpromoted ion exchanger catalysts

Abstract: Previously evaluated kinetics of the synthesis of bisphenol A on ion exchanger catalyst modified by partial neutralization of its acidic groups by 2-mercaptoethylamine was compared with kinetics of this reaction on unmodified ion exchanger. Beside the differences in observed reaction rates, there was found only a small influence of the promoter on the form of the kinetics. The effect of 2-mercaptoethylamine as a heterogenized promoter, corrected for the influence of the diminishing of the concentration of acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A number of groups have disclosed the utility of using mixed thiol/sulfonic acid catalytic systems to enhance activity and selectivity. However, Cheng and co-workers reported recently that catalysts containing incompletely oxidized sulfur species exhibited lower catalytic activity . From the data given in Table , the acid capacity of the propylsulfonic acid modified materials is always less than the sulfur elemental analyses, and this could indicate the presence of nonsulfonic acid sites on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…A number of groups have disclosed the utility of using mixed thiol/sulfonic acid catalytic systems to enhance activity and selectivity. However, Cheng and co-workers reported recently that catalysts containing incompletely oxidized sulfur species exhibited lower catalytic activity . From the data given in Table , the acid capacity of the propylsulfonic acid modified materials is always less than the sulfur elemental analyses, and this could indicate the presence of nonsulfonic acid sites on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of thiols as a cocatalyst is known to improve both the rate of reaction and the selectivity to the desired isomer. 3,4 Mineral acids can be used to catalyze the bisphenol condensation reaction, but solid acid catalysts such as polymeric ionexchange resins are typically used for commercial bisphenol A production due to their recyclability. Thiols have been either added as a homogeneous feed additive 4 or bound to the resin surface by ion-pairing.…”
Section: Introductionmentioning
confidence: 99%
“…They are synthesized by the acid-catalyzed condensation between a ketone and phenol, yielding the desired p , p ′ isomer and a byproduct, the o,p ’ isomer (Scheme ). The addition of thiols as a cocatalyst is known to improve both the rate of reaction and the selectivity to the desired isomer. , …”
Section: Introductionmentioning
confidence: 99%
“…Acid-catalyzed coupling reactions of LA with phenol proceed via protonation of the ketone which subsequently reacts with phenol to form DPA. Of particular importance is the acid-thiol cooperative catalytic action of sulfonic acid-functionalized catalysts and thiol-containing compounds, first demonstrated for the condensation of acetone and phenol to BPA. Recently, we reported that the combination of sulfonated hyperbranched poly(arylene oxindole)s (SHPAOs) and thiol promoters allows the catalytic synthesis of DPA in high yields (>50%) . The SHPAOs possess a high Brønsted acid density (4.3 mmol H + g –1 ), a high solubility in polar solvents and a low solution viscosity, which explains the growing interest for their use in catalytic applications. ,, To facilitate the reuse of the catalyst, we aimed to incorporate thiol promoters into the hyperbranched polymer matrix by neutralization of the sulfonic acid groups via ionic bonding with 2-aminoethanethiol or 2-(4-pyridyl)ethanethiol .…”
mentioning
confidence: 99%